Highly Oxidising Conditions in Volatile-Rich El Hierro Magmas: Implications for Ocean Island Magmatism. (21st February 2022) - Taracsák, Zoltán; Longpré, Marc-Antoine; Tartèse, Romain; Burgess, Ray; Edmonds, Marie; Hartley, Margaret E
Abstract: Recent studies investigating magmatic volatile contents indicate widespread enrichment of carbon, sulfur, and halogens in ocean island basalts (OIBs). At El Hierro in the Western Canary Islands, magmas with exceptionally high CO2 and S contents have been erupting throughout the Holocene. High S content of up to 5200 ppm requires an oxidised mantle source, but estimates of initial magmatic oxygen fugacity ( f O2 ) are sparse. Here, we present estimates of f O2 and magmatic temperature for El Hierro together with a global mantle potential temperature dataset to evaluate redox and temperature conditions in the early stages of melt evolution for volatile-rich OIBs. Oxygen fugacities calculated using vanadium partitioning between melt inclusions (MIs) and their olivine hosts are >FMQ + 2.9 (2.9 log10 units above the fayalite-magnetite-quartz buffer), indicating that El Hierro magmas are highly oxidised. MI and matrix glass sulfur speciation data record f O2 between FMQ-1 to FMQ + 2; these values strongly depend on the position of the S 2− to S 6+ transition relative to the FMQ buffer. Nonetheless, glass sulfur speciation data record lower oxygen fugacity than V partitioning data, indicating MIs were able to maintain Fe 3+ /ΣFe and S 6+ /ΣS equilibrium with the surrounding melt during their evolution. The high f O2 of El Hierro magmas is coupled with an average mantle potential temperature estimate of 1443 ± 66°C (1σ, n  = 17) for the broader Canary Islands, which is slightly higher than the average potential temperature estimated for adjacent mid-ocean ridge segments (1427 ± 33°C, 1σ, n  = 474), albeit the two values are well within error. We find that ~98% of Canary Island rock compositions are not suitable for calculation of mantle potential temperatures using currently available methods. This is caused by the presence of substantial pyroxenite and volatile-enriched peridotite mantle domains under the Canary Islands. A wider compositional calibration of various petrological models is necessary to precisely determine mantle potential temperatures for volatile-rich alkali basalts. Our high oxygen fugacity estimates for El Hierro magmas reflect the fertile, fusible, and volatile-enriched nature of the mantle source beneath the Western Canary Islands.